Extended Threshold Error Correction Model of economic growth in Israel - Osińska, Magdalena; Gałecki, Maciej; Boehlke, Jerzy; Fałdziński, Marcin; Khan, Atif Maqbool; Shachmurove, Yochanan (Bulletin of Geography. Socio-economic Series, 2022)
The paper utilizes a comprehensive approach to threshold cointegration to analyse the Israeli per capita Gross Domestic Product (GDP) growth dynamics. The time-series data for the years 1980–2019 are taken. The study uses a two-regime threshold error correction model (TECM) to test short- and long-term growth factors. The results reveal that Research and Development (R&D) expenses measured as a percentage of GDP are the primary driving force in the long and short term. The threshold value of 3.25% of GDP exhibits a substantial difference between the two regimes corresponding to the development phases of the Israeli economy. The results are validated using various tests for threshold models. The general conclusion is that the applied hierarchical procedure for TECM model construction is robust and universal for modeling economic growth. The results allow the formulation of policy implications.